Comparative Genomic Analysis and Clinical Outcomes of BRAF -mutated Advanced Biliary Tract Cancers - Tang, Tin-Yun; Nichetti, Federico; Kaplan, Ben; Lonardi, Sara; Pietrantonio, Filippo; Salvatore, Lisa; Vivaldi, Caterina; Rimassa, Lorenza; de Braud, Filippo; Rizzato, Mario Domenico; Pavlick, Dean; Chu, Randy; et al. (Clinical cancer research, 2023)
BRAF mutations are rare in biliary tract cancers (BTC), but are of interest given the recent developments in targeted therapy for BTC. We investigated the clinical outcomes in a cohort of BRAF-mutant advanced BTC treated with first-line chemotherapy. Furthermore, we investigated the genomic landscape of BRAF class I, II, and III mutations in the intrahepatic cholangiocarcinoma (iCCA) subgroup of BTC. We analyzed two nonoverlapping cohorts. We examined the genomic landscape of BRAF-mutated iCCA in a "genomic cohort" [187 class I, 82 class II, 113 class III BRAF mutants and 8,026 wildtype (WT)]. We also analyzed median progression-free survival (PFS) and overall survival (OS) on first-line chemotherapy in a separate multi-institutional "clinical cohort" of patients with BTC (including iCCA and extrahepatic cholangiocarcinoma (eCCA) and gallbladder cancer; 41 class I, 32 class II+III BRAF mutants and 1,042 WT). In the entire BTC clinical cohort, the median PFS was shorter for class I [HR, 2.11 (P < 0.001)] and class II+III [HR, 1.72 (P = 0.007)] as compared with BRAF WT. OS was also shorter in class I [HR, 2.04 (P = 0.011)] and class II+III [HR, 1.86 (P = 0.002)] as compared with BRAF WT. In the iCCA subgroup, class I alterations were mutually exclusive with FGFR2, IDH1/2, ERBB2, and KRAS mutations. Class II+III mutations appear to be mutually exclusive with FGFR2 and KRAS. In BTC, all classes of BRAF mutations are associated with a worse prognosis. BRAF mutations occur in 5% of iCCA subgroup and may be mutually exclusive with other targetable mutations.